Understanding the impact of moxifloxacin on immune function: Findings from cytokine analyses and immunological assays in mice - Mehmood Ahmad; Naeem Rasool; Rana Muhammad Zahid Mushtaq; Sammina Mahmood; Abdur Rauf Khalid; Waqas Ahmad; Bilal Mahmood Beg; Mostafa A. Abdel Maksoud; Abdul Aziz Alamri; Adeel Sattar (PLoS ONE, 2025)
(1) Background: Moxifloxacin (MXF) is a fluorinated quinolone antibiotic used most commonly due to its broad spectrum of activity. However, the immunomodulatory effects of MXF remain underexplored. This study aims to investigate the patterns of immunomodulatory effects. (2) Methods: Swiss female albino mice were treated with different concentrations of MXF, and the immunological studies were performed using a cytokine assay, carbon clearance test, indirect hemagglutination test, and a mice lethality assay. (3) Results: Results revealed that MXF mitigated cyclophosphamide-induced leukopenia, with TLC reduced less at 7.5 mg/kg (5.37 ± 0.6) compared to 3.75 mg/kg (2.95 ± 0.485) and 15 mg/kg (2.14 ± 0.104). Results of the phagocytic index showed significantly lower clearance rates in the 7.5 mg/kg (0.01600 ± 0.00175) and 15 mg/kg (0.01331 ± 0.00310) groups compared to the control. Ex-vivo mice macrophages cytokines analysis showed elevated TGF-β1 levels in the MXF 32 µg/ml group (30.826 ± 0.817pg/ml) and IL-10 levels in the MXF 16 µg/ml group (50.427 ± 0.786pg/ml). The MXF 64 µg/ml treated group showed significantly lower IL-6 (8.714 ± 0.647pg/ml) and TNF-α (28.81 ± 3.24pg/ml) levels compared to controls. Findings of indirect hemagglutination assay showed higher antibody titers in the 3.75 mg/kg group (7.200 ± 0.374) compared to higher doses, whereas dose-dependent mortality was observed, with the highest mortality at 15 mg/kg (80%) in the mice lethality assay. (4) Conclusions: MXF exhibited notable immunomodulatory effects by mitigating cyclophosphamide-induced immunosuppression, modulating cytokine levels, phagocytic activity, and antibody production. The findings suggested that MXF could be considered for managing immunosuppression.